A lncRNA survey finds increases in neuroprotective LINC‐PINT in Parkinson's disease substantia nigra. Issue 3 (20th February 2020) - Simchovitz, Alon; Hanan, Mor; Yayon, Nadav; Lee, Songhua; Bennett, Estelle R.; Greenberg, David S.; Kadener, Sebastian; Soreq, Hermona
Abstract: Recent reports highlight regulatory functions of long noncoding RNAs (lncRNAs) in neurodegeneration and aging, but biomedical implications remain limited. Here, we report an rRNA‐depletion‐based long RNA‐Sequencing Resource of 65 substantia nigra, amygdala, and medial temporal gyrus samples from Parkinson's disease (PD) and matched control brains. Using a lncRNA‐focused analysis approach to identify functionally important transcripts, we discovered and prioritized many lncRNAs dysregulated in PD. Those included pronounced elevation of the P53‐induced noncoding transcript LINC‐PINT in the substantia nigra of PD patients, as well as in additional models of oxidative stress and PD. Intriguingly, we found that LINC‐PINT is a primarily neuronal transcript which showed conspicuous increases in maturing primary culture neurons. LINC‐PINT also accumulated in several brain regions of Alzheimer's and Huntington's disease patients and decreased with healthy brain aging, suggesting a general role in aging and neurodegeneration for this lncRNA. RNAi‐mediated depletion of LINC‐PINT exacerbated the death of cultured N2A and SH‐SY5Y cells exposed to oxidative stress, highlighting a previously undiscovered neuroprotective role for this tumor‐inducible lncRNA in the brains of patients with neurodegenerative disorders. Abstract : We performed RNA‐Seq on a large cohort of brain tissues from Parkinson's disease patients and controls. Next, we applied a novel lncRNA‐based analysis method to the data to screen for functionally relevant lncRNAs, identifying LINC‐PINT. Comparison to other models identified LINC‐PINT as a neuronal transcript dysregulated in additional neurodegenerative diseases and in brain aging. Finally, functional analysis revealed LINC‐PINT to be neuroprotective in the context of oxidative stress.